Use of nanotechnologies in poultry - Avramenko, І. V. (БГАТУ, 2021)
In organizing the effective marketing of poultry products, their safety and high quality play an important role. The urgency of this problem is due to the increased attention of the population to a healthy lifestyle. Only clean food products of the industry, high quality and environmental friendliness of which are confirmed by international standards, can attract the consumer and provide the enterprise with profit, which has become a prerequisite for successful and effective entrepreneurship. It is high-quality products, especially enriched with nutrients and microelements, that are now becoming the defining criterion for the competitiveness of a poultry enterprise. The presence of a certificate is a kind of pass to the poultry products market, as well as a guarantee of the good quality and safety of the finished product for the buyer
Keywords: poultry products; ecological poultry farming; competitiveness of poultry farms